The Influence of Emotional Intelligence on University Students' Interpersonal Communication - Seneru, Wistina; Dharma, Yudi; Wati, Rima (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2024)
This study explores the important relationship between emotional intelligence (EI) and interpersonal communication among students of Jinarakkhita Buddhist College of Lampung, particularly in the Communication Studies program during the 2023/2024 academic year. Recognizing a significant gap in understanding how EI affects communication dynamics in academic contexts, this study aimed to uncover the relationship. Using a quantitative approach, data was collected from a sample of 45 students using a structured questionnaire. A significant positive correlation was found between EI and interpersonal communication effectiveness through Pearson correlation analysis and simple linear regression with Microsoft Excel. Specifically, college students who exhibited higher levels of EI showed better adaptive and cooperative behaviors in their interactions. This study confirms the importance of EI development among university students to improve interpersonal communication, with potential implications for future education and professional preparation. With the increasing recognition of emotional intelligence in educational contexts, this study provides valuable insights and recommends curriculum development and student engagement strategies.